Effect of diabetes on life expectancy in the United States by race and ethnicity. (3rd April 2018) - Preston, Samuel H.; Choi, Daesung; Elo, Irma T.; Stokes, Andrew
ABSTRACT: We investigated the impact of diabetes on US life expectancy by sex and race/ethnicity using a prospective cohort study design. Cohorts were drawn from 1997 to 2009 waves of the National Health Interview Survey and linked to death records through December 31, 2011. We combined data on the prevalence of diabetes among decedents with estimates of the hazard ratios of individuals diagnosed with diabetes to calculate population attributable fractions (PAFs) by age, sex, and race/ethnicity at ages 30 and above. These estimates were then applied to deaths in the official US life table for 2010 to estimate effects of diabetes on life expectancy. Diabetes was responsible for a reduction of 0.83 years of life expectancy for men at age 30 and 0.89 years for 30-year-old women. The impact was greatest among Black women at 1.05 years. Estimates based on traditional demographic and actuarial methods using the frequency with which a disease appears as an underlying cause of death on death certificates produced a reduction in life expectancy at age 30 of only 0.33 years. We conclude that diabetes is substantially reducing US longevity and that its effect is seriously underestimated when using data on underlying causes of death.